Modeling of direct band-to-band tunneling in one-sided pn junctions based on Kane’s model - Nguyễn, Đăng Chiến (Bach Khoa Publishing House, 2024)
Recently, the band-to-band tunneling (BTBT) has been employed as a main mechanism to produce the conduction current in tunnel field-effect transistors (TFETs) which are currently considered as a potential candidate for low power integrated circuits because of their achievable sub-60 mV/decade subthreshold swing at room temperature. Based on the Kane model, this study presents the calculation of direct BTBT currents in one-sided p/n junctions, including p/n++ and n/p++ junctions, which are basic tunnel junctions in typical TFET devices. It is shown that the calculated current-voltage curves of the two junctions are symmetric with each other because of the symmetry of all material and structure parameters of the two devices. The calculation methods of BTBT currents in the one-sided p/n junctions can be applied for computing the tunneling current, studying the device physics and characteristics of TFETs operated in both n- and p-type modes.